Training on Abacus-Based Mental Calculation Enhances Visuospatial Working Memory in Children - Wang, Chunjie (J Neurosci, 2019)
Abacus-based mental calculation (AMC) involves temporary storage and manipulation of an imaginary abacus closely related to the function of visuospatial working memory (VSWM). The present study thus investigated the effects of AMC training on VSWM and its neural correlates. A total of 144 human subjects (67 boys) were assigned to AMC or control groups at their entry to primary school. The AMC group received 2 h AMC training per week for 5 school years, whereas the control group spent the time in activities, such as conventional calculation and reading. Raven's Intelligence Test was administered both before and after training. Two arithmetic tests and a VSWM task were conducted after training. Among these participants, fMRI data were collected from 64 children for the VSWM task. Behavioral results indicated that the AMC group outperformed controls on both arithmetic and VSWM tasks, but not on Raven's Intelligence Test. While the two groups activated similar regions during the VSWM task, the AMC group showed greater activation than the controls in frontal, parietal, and occipital areas. Interestingly, the activation of right middle frontal gyrus mediated the relation between the arithmetic ability and the VSWM performance in the AMC group, suggesting that the frontal region may be the neural substrate underlying the transfer effect from AMC training to VSWM. Although the transfer effects seem quite limited considering the length and intensity of the training, these findings suggest that long-term AMC training not only improves arithmetic ability but also has a potential positive effect on VSWM. SIGNIFICANCE STATEMENT Plasticity of working memory is one of the most rapidly expanding research fields in the developmental and cognitive sciences. Previous studies suggest that abacus-based mental calculation (AMC) relies on a visuospatial imaginary strategy, which is closely related to visuospatial working memory (VSWM). However, the impacts of AMC training on VSWM and the underlying neural basis remain unclear. Here, we found that AMC training enhanced VSWM in children, which was accompanied by altered activation in frontal, parietal, and occipital areas. Moreover, we observed that activation in right middle frontal gyrus played a significant mediation role in the transfer of AMC training to VSWM. These findings provide a new perspective to VSWM training and also advance our understanding of related brain plasticity.